Choosing the Optimal Method for Measuring Glomerular Filtration Rate in Pediatric Intensive Unit - Semen N. Averyanov; Valerij G. Аmcheslavskiy; Vladimir G. Bagaev; Rustem F. Tepaev (Педиатрическая фармакология)
The measurement of glomerular filtration rate (GFR) in intensive care unit patients is strategically important and determines the further treatment tactics. The article provides a literature review on choosing the various methods for assessing the glomerular filtration rate in children with kidney injury. We identified the main limitations of creatinine as a marker for measuring GFR; the features of laboratory methods for creatinine determination were detected.